Pengaruh Fleksibilitas Kerja Dan Spesialisasi Pekerjaan Terhadap Kinerja Karyawan (Studi Kasus Pada CV. Lestari Plastik Pagak Malang) - Wanda Yunita Pramesti; Nurhidayah Nurhidayah; Achmad Agus Priyono (UNIVERSITAS ISLAM MALANG, 2022)
AbstractThis study aims to determine the effect of work flexibility and work specialization on employee performance at CV. Sustainable Plastic Pagak Malang. The location of this research was conducted on employees of CV. Sustainable Plastic Pagak Malang. This research is a quantitative research. This research uses a case study method where data is obtained by distributing questionnaires to employees of CV. Lestari Plastik Pagak Malang was chosen using probably sampling with random sampling, namely random sampling from the population because the population is considered homogeneous and in the determination of the sample, 50 employees are produced. Data were analyzed using multiple linear regression test and determination test. Based on the results of data analysis, the results of the t-test indicate that work flexibility affects the performance of CV employees. Sustainable Plastics Pagak Malang. And work specialization has an effect on employee performance CV. Sustainable Plastics Pagak Malang. The results of the determination test show that the percentage is 40.6%, where employee performance is able to be influenced by work flexibility and work specialization. Furthermore, in this study, the data collection method can be continued by paying attention to the willingness of employees and focusing on distributing online questionnaires to respondents, although they are still contacted personally and the researcher's telephone number is included, so if the respondent wants to ask questions, they can contact the researcher. Keywords: Employee Performance, Work Flexibility, Job Specialization